Orbital Stability of Solitary Waves for Generalized Zakharov System (Journal of Partial Differential Equations, 2007)
This paper considers the stability of the solitary waves for the generalized Zakharov system. By applying the abstract theory of Grillakis M. et al. and detailed spectral analysis, we obtain the stability of the solitary waves.
Keywords: Solitary waves; orbital stability; generalized Zakharov system